2016
DOI: 10.18172/cig.2948
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal patterns of meteorological droughts in the Balearic Islands (Spain)

Abstract: ABSTRACT. The Balearic Islands is a region highly prone to suffer meteorological and hydrological droughts, mainly due to the high intra-and inter-annual variability of precipitation, and the high water consumption associated to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…In continental Spain, Vicente-Serrano et al (2014b) showed a general decrease in relative humidity from the decade of 1960, mainly associated with a general decrease in the moisture transport to the Iberian Peninsula as well as a certain precipitation decrease. Similarly, Espadafor et al (2011) and Vicente-Serrano et al (2014b) showed that the strong increase in ET o in the last decades is associated with the relative humidity decrease due to air temperature rise, which caused more severe drought events (Coll et al, 2016;Lorenzo-Lacruz and Morán-Tejeda, 2016; Peña- Gallardo et al, 2016). In the Canary Islands, no precipitation changes have been identified during the analysed period (Sánchez-Benitez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In continental Spain, Vicente-Serrano et al (2014b) showed a general decrease in relative humidity from the decade of 1960, mainly associated with a general decrease in the moisture transport to the Iberian Peninsula as well as a certain precipitation decrease. Similarly, Espadafor et al (2011) and Vicente-Serrano et al (2014b) showed that the strong increase in ET o in the last decades is associated with the relative humidity decrease due to air temperature rise, which caused more severe drought events (Coll et al, 2016;Lorenzo-Lacruz and Morán-Tejeda, 2016; Peña- Gallardo et al, 2016). In the Canary Islands, no precipitation changes have been identified during the analysed period (Sánchez-Benitez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…AENA, the airport operator in Spain, recognized total water withdrawals of 484,000 m 3 in the airport in 2018. It is evident that the increasing cruise activity in the western Mediterranean ports has an impact on freshwater resources and especially on islands where water is scarce and intense droughts occur [20][21][22]39]. The threat of climate change, with longer and more intense dry periods, emphasizes the rational use of water for activities such as cruise ship tourism that has a growing social context in the Balearic Islands (e.g., more than 10,000 Majorcan residents signed a petition calling for a limit of one cruise ship a day docking in Palma, and there have been several anti-cruise ship protests).…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, 12.5 million tourist arrivals were recorded (IBESTAT 2017b) in this top touristic destination, which has a temperate climate and attractive beaches, good accessibility and massive touristic infrastructure, including hotels and a large airport. Unfortunately, the tourist activity clashes with one of the most important socio-environmental issues of the territory: water scarcity [2][3][4]. The Balearic Islands face a severe water supply problem, mainly during summer months.…”
Section: Study Area and Backgroundmentioning
confidence: 99%
“…The Balearic Islands face a severe water supply problem, mainly during summer months. As a Mediterranean archipelago, climate drives natural variability in both seasonal and inter-annual precipitation, and this leads to frequent drought episodes [3] that may compromise water supply. The overexploitation and salinization of groundwater resources and the increasing dependence on desalinated water is well documented [5][6][7][8].The current mix of water sources on the islands reflects the technological and managerial approach to anthropogenic pressures on scarce water resources.…”
Section: Study Area and Backgroundmentioning
confidence: 99%